Elementary New Testament Greek - Ewald, Owen (Open textbook library., 2022)
This open-access textbook helps students learn to read New Testament Greek at the elementary level. It includes clear, concise explanations of grammar and syntax, helpful examples, and essential vocabulary, with no assumption of previous language study, and it does not require accents for most forms. At the end of each of its twenty chapters, students will find short Greek-language episodes from the life of a fictional early Christian family of Jewish ancestry, short readings from the Greek New Testament and Septuagint, and review/homework exercises that can help reinforce new concepts and vocabulary. This book can help students prepare to read Nijay Gupta and Jonah Sandford’s Intermediate Greek Reader: Galatians and Related Texts, also available as an open-access textbook.